Von Willebrand Factor Multimer Densitometric Analysis: Validation of the Clinical Accuracy and Clinical Implications in Von Willebrand Disease. Issue 3 (17th March 2021) - Boender, Johan; Atiq, Ferdows; Cnossen, Marjon H.; van der Bom, Johanna G.; Fijnvandraat, Karin; de Meris, Joke; de Maat, Moniek P. M.; van Galen, Karin P. M.; Laros-van Gorkom, Britta A. P.; Meijer, Karina; Eikenboom, Jeroen; Leebeek, Frank W. G.
Abstract : Von Willebrand factor (VWF) multimer analysis is important in the classification of von Willebrand disease (VWD). Current visual VWF multimer analysis is time consuming and inaccurate in detecting subtle changes in multimer patterns. Although VWF multimer densitometric analysis may be useful, the accuracy needs further investigation before it can be widely applied. In this study we aimed to validate VWF multimer densitometric analysis in a large cohort of VWD patients and to identify patient characteristics associated with densitometric outcomes. Patients were included from the Willebrand in the Netherlands (WiN) study, in which a bleeding score (BS) was obtained, and blood was drawn. For multimer analysis, citrated blood was separated on an agarose gel and visualized by Western blotting. IMAGEJ was used to generate densitometric images and medium-large VWF multimer index was calculated. We included 560 VWD patients: 328 type 1, 211 type 2, and 21 type 3 patients. Medium-large VWF multimer index performed excellent in distinguishing visually classified normal VWF multimers from reduced high-molecular-weight (HMW) multimers (area under the curve [AUC]: 0.96 [0.94-0.98], P < 0.001), normal multimers from absence of HMW multimers (AUC 1.00 [1.00-1.00], P < 0.001), and type 2A and 2B from type 2M and 2N (AUC: 0.96 [0.94-0.99], P < 0.001). Additionally, higher medium-large VWF multimer index was associated with lower BS in type 1 VWD: β = -7.6 (-13.0 to -2.1), P = 0.007, adjusted for confounders. Densitometric analysis of VWF multimers had an excellent accuracy compared with visual multimer analysis and may contribute to a better understanding of the clinical features such as the bleeding phenotype of VWD patients.